2016
DOI: 10.1371/journal.pone.0148172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Screening Test Kits for G6PD Enzyme Deficiency: Implications for Its Use in the Radical Cure of Vivax Malaria in Remote and Resource-Poor Areas in the Philippines

Abstract: ObjectiveWe evaluated a battery of Glucose-6-Phosphate Dehydrogenase diagnostic point-of-care tests (PoC) to assess the most suitable product in terms of performance and operational characteristics for remote areas.MethodsSamples were collected in Puerto Princesa City, Palawan, Philippines and tested for G6PD deficiency with a fluorescent spot test (FST; Procedure 203, Trinity Biotech, Ireland), the semiquantitative WST8/1-methoxy PMS (WST; Dojindo, Japan) and the Carestart G6PD Rapid Diagnostic Test (CSG; Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…Philippines by using Trinity Biotech G6PD kit. 18 Apart from age group involved in the studies, the differences in quantitative values of G6PD activity may also be due to the different comercial kits used. LaRule, et al reported that reference values vary widely depending on the reference tests used.…”
Section: Discussionmentioning
confidence: 99%
“…Philippines by using Trinity Biotech G6PD kit. 18 Apart from age group involved in the studies, the differences in quantitative values of G6PD activity may also be due to the different comercial kits used. LaRule, et al reported that reference values vary widely depending on the reference tests used.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of phenotyping and genotyping was used for several reasons. Firstly, the FST accurately diagnoses severe G6PD deficiency [23] at activity levels below 30% of population median, but its positive predictive value is still likely to be low when the population prevalence of deficiency is low. Hence a second test to confirm the presence of a genotype compatible with deficiency was required.…”
Section: Discussionmentioning
confidence: 99%
“…Hence a second test to confirm the presence of a genotype compatible with deficiency was required. Secondly, consideration of only cases with clear deficiency on the FST was likely to be insensitive for detection of cases with intermediate levels of G6PD activity seen in a proportion of female heterozygotes [23, 29, 30]. For this reason, all cases with an intermediate result on the FST were genotyped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this challenge, there have been attempts to develop commercially available rapid screening tests for G6PD deficiency. Recent studies have identified there are a number of short‐comings associated with these tests: low sensitivity (<85%) for detecting individuals with moderate and severe deficiency, a high degree of false G6PD normal results in males and heterozygous females, and difficulty interpreting the readout signal …”
Section: Discussionmentioning
confidence: 99%